Proyecto de factibilidad para creación de un bar karaoke en la ciudad de Zumba, cantón Chinchipe, provincia de Zamora Chinchipe - Salazar Paz, Diana Carolina (2016)
This research aims to make a Draft Feasibility creating a Karaoke Bar in the city of Zumba, Canton Chinchipe province of Zamora Chinchipe, which consists of four major studies such as: Market Research, Technical Study, Study organizational, Financial Studies and Financial evaluation; through which we know the feasibility or not the same. The implementation of this bar-karaoke allowed the application of different methods such as: inductive, deductive, analytical, statistical, using survey research techniques and direct observation. It was necessary to develop a market study, which by applying 382 surveys to residents of the sector, in order to determine whether there was indeed an unsatisfied demand could be harnessed to offer service Bar-karaoke. The marketing plan search tactics allowed to enter the market by analyzing the product, price, place and production as well as other aspects related to the functioning of the establishment. The technical study allowed us to determine the location of the place, ideal for project implementation, likewise possible to quantify the size, installed capacity and other technical aspects that needed to know. In the Organizational study it found the establishment as a limited liability company with the legal name "THE HIDING PLACE" BAR - KARAOKE, which consists of two shareholders. Moreover, this study also allowed us to determine the need to hire a manager, a secretary, a bartender a D. J two kitchen helpers and services, generating employment positions for this sector. The initial investment of the project is $ 49,278.06 which will be funded in a 66.19% ($ 32,615.72) and the remaining 33.81% (16,662.34) with its own funds. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 315,320.99, indicating that the project or investment is suitable. For this project, the IRR is 79.6% and this satisfactory value for the project, the time it would take to recover the original investment would be one year, 6months to 7 days. Well the benefit / cost, relationship shows that for every dollar invested, a return of $ 1.17 is obtained. Sensitivity analysis gives us less than one values, so the changes in costs and revenues increased 50% and decreased by 30%, respectively, did not affect the project . Finally, and as evidenced by the financial indicators it is found that the implementation of this project is feasible to run, determining conclusions and recommendations.